Porcine sapelovirus among diarrhoeic piglets in India. Issue 1 (27th February 2017) - Ray, P. K.; Desingu, P. A.; Kumari, S.; John, J. K.; Sethi, M.; Sharma, G. K.; Pattnaik, B.; Singh, R. K.; Saikumar, G.
Summary: Porcine sapelovirus (PSV) A belongs to the genus Sapelovirus, family Picornaviridae. PSV infections in pigs have been reported from European countries, United States, Japan, China, Korea and Brazil. The virus has been isolated/detected from faeces of healthy pigs as well as those affected with diarrhoea, respiratory signs, encephalitis, skin lesions and fertility disorders. This study was planned to investigate whether PSV is prevalent among pigs in India and to characterize PSV encountered in the study population. The study revealed that five of 70 (7.14%) faecal samples were found positive for PSV using RT‐PCR. Three viruses were successfully isolated from faecal samples using IB‐RS‐2 cell line. Complete genome sequencing and analysis of one Indian PSV isolate revealed highest homology (88%) with V13 strain from England. Phylogenetic analysis of the complete polyprotein nucleotide sequences of 14 strains of PSV classified the viruses into four distinct clades. This first report from India adds to our knowledge on genetic diversity of PSV detected so far among pigs in different countries. A large‐scale surveillance of the virus is required to understand its genomic diversity and economic impact.